Gambaran Pengetahuan, Sikap, dan Tingkat Kecemasan Masyarakat tentang Kejadian Covid-19 di Lingkungan Perumahan Taman Banten Lestari Kota Serang Tahun 2020 - Ghina Salsa Bela; Lenny Stia Pusporini; Nila Marwiyah; Bambang Kuntarto (Universitas Faletehan, 2021)
Coronavirus Disease (Covid-19) is spreads widely and rapidly to several countries of the world, resulting in an increased number of people infected by Covid-19 every day. The purpose of this study was to identify the depiction of public knowledge, attitudes and anxiety level regarding Covid-19 occurrence at Taman Banten Lestari Residence in 2020. The study design used was observational description with number of subject were the communities who live in Taman Banten Lestari Residence Block D RW 21. The sampling technique was purposive sampling, with total 84 respondents. The frequency descriptive-based research result showed that most of respondent (53.6%) had a good knowledge, (54.8%) had a positive attitude and (67.9%) had a mild anxiety. Health workers should continually educate public about Covid-19 to improve knowledge, positive attitude and to decrease the level of anxiety of community, so that people are more alert to Covid-19 occurrence.